Clinical efficacy of surgical versus conservative treatment for multiple rib fractures: A meta-analysis of randomized controlled trials. (November 2020) - Long, Rui; Tian, Junying; Wu, Shasha; Li, Yang; Yang, Xiuhua; Fei, Jun
Abstract: Background: There are still controversies between surgical treatment and conservative treatment for multiple rib fractures (MRFs). No consensus has been reached concerning the indications and timing of surgery. In this meta-analysis, we aimed to determine the optimal treatment for MRFs. Methods: Six databases (PubMed, Medline, Embase, Cochrane, Cnki, Wanfang Database) were retrieved for all eligible randomized controlled trials (RCTs) published before January 2020. MRFs were treated either with operative reduction and internal fixation or conservative treatment. The pertinent data were retrieved. The quality of RCTs was evaluated by the modified Jadad rating scale and meta-analysis was performed using RevMan 5.3 software. Results: Seven RCTs involving 538 MRFs patients (260 were treated surgically vs. 278 conservatively) were included in this meta-analysis. Compared with conservative treatment, surgical treatment resulted in shorter length of hospital stay (WMD -8.48; 95% CI -11.34 to −5.63; P  < 0.001), length of ICU stay (WMD -5.72; 95% CI -7.31 to −4.13; P  < 0.001) and duration of mechanical ventilation (WMD -4.93; 95% CI -8.79 to −1.07; P  = 0.01), with a lower risk of complications including pneumonia (RR 0.40; 95% CI 0.30 to 0.53; P  < 0.001) and chest wall deformity (RR 0.07; 95% CI 0.03 to 0.14; P  < 0.001). The sensitivity analysis carried out by excluding one study with significant heterogeneity showed that the rate of tracheostomy was lower in the surgical group than in the conservative group (RR 0.44; 95% CI 0.28 to 0.71; P  = 0.0008). Conclusions: For patients with MRFs, surgical treatment resulted in faster recovery, a lower risk of complications and better prognosis than conservative treatment. Graphical abstract: Image 1 Highlights: For patients with MRFs, surgical treatment resulted in faster recovery, a lower risk of complications and better prognosis. The development of medical science didn't result in reduction of hospital length of stay and incidence of pneumonia. The conclusions on mortality varied among meta-analyses by different researchers.